Analysis of peripheral leucocyte populations in N'Dama and Boran cattle following a rechallenge infection with Trypanosoma congolense - Williams, D.J.L.; Naessens, Jan; Scott, J.R.; McOdimba, F.A. (Wiley, 1991)
Summary Monoclonal antibodies, flow cytometry and routine hacmatological techniques were used to analyse circulating leucocyte populations in trypanotoler‐ant (N'Dama) and trypanosusceptible (Boran) cattle following a homologous rechallenge with Trypanosoma congolense clone 1L13‐E3. The N'Damas developed a low, transient parasitaemia and did not develop anaemia. The Borans became parasitaemic and developed chronic anaemia but three of the five animals eventually self‐cured, whilst, a group of primary‐challenged Borans experienced a severe infection characterized by high levels of parasilacmia and acute anaemia.During infection the numbers of circulating B‐cells increased in all three groups from day 21 onwards. The proportion of B‐cells expressing the CD5 antigen increased from pre‐infection levels of 5‐10% of B‐cells to 49‐90% by day 19 post infection in all three groups. The neutrophil count declined in both Boran groups but not in the N'Damas. The CD4+ T‐cell and γδ T‐cell populations decreased in both Boran groups but did not alter significantly in the N'Damas. Although it was not possible to infer from the data, that the CD4+, γδ T‐cell, neutrophil and erythrocyte populations were directly responsible for the differential control of the disease by the two breeds, it was possible to correlate alterations in these cell populations with the severity of the disease.